A MILP approach for the operational optimization of gas networks. Issue 9 (2022) - Ghilardi, Lavinia Marina Paola; De Pascali, Matteo Luigi; Casella, Francesco; Barbati, Daniele; Palazzo, Roberto; Martelli, Emanuele
Abstract: Nowadays, natural gas is one of the primary energy resources employed in many sectors, and it can be regarded as a bridge fuel in the decarbonization process. The transport of natural gas relies on a complex infrastructure, which needs to be properly managed to minimize energy consumption and CO2 emissions. This study proposes a Mixed Integer Linear Programming formulation capable of optimizing the unit commitment (on/off) of the gas-turbine-driven compressors, their loads and the dynamic operation of the network. The gas network dynamic model has been discretized in space and time, and the friction term has been linearized. The performance maps of the gas-turbine-driven compressors have been linearized using the convex-hull approach. The model includes all the technical limitations of the gas-turbine-driven compressors and it can handle flow reversals on all pipes. Moreover it is suitable for cyclic networks. The MILP model is applied to a case study with 4 compressor stations, each containing multiple gas turbine driven compressors, and a cyclic network consisting of 29 pipes.